Development of PCR-based method for detection of Enterobacteriaceae in septicemia - Hossein Fazzeli; Mohammad Reza Arabestani; Bahram Nasr Esfahani; Farzin Khorvash; Mohammad Reza Pourshafie; Sharareh Moghim; Hajieh Ghasemian Safaei; Jamshid Faghri; Tahmine Narimani (Journal of Research in Medical Sciences, 2012)
Objective: Sepsis is a systemic inflammatory response associated with high mortality rates in the clinical setting. A multiplex endpoint polymerase chain reaction (PCR) based assay for rapid detection of enterobacteriaceae involved in septicemia, which included Internal Control (IC) and 16S rDNA, is presented here. To develop a panel of primers for DNA fragments of 16S rDNA, enterobacteriaceae, IC, and evaluate analytical sensitivity and specificity of the test Materials and Methods: Primers for amplification of enterobacteriaceae, IC, and16S rDNA were designed, and then PCR was performed. Minimal analytical sensitivity was determined by cloning and colony PCR, and specificity was tested on the basis of their respective standard strains. This study is a cross-sectional Model. Results: Our results showed the rpoB gene as the most promising target for detection of enterobacteriaceae by PCR amplification. Specificity and sensitivity of endpoint PCR were 100%, 100%, and 100%, and 10, 1, and 100 copies/reaction for enterobacteriaceae, IC, and 16S rDNA, respectively . Conclusion: The molecular panel presented offers the advantage of an easy, reliable, and cost-effective system when compared to other molecular detection methods. However, further evaluation is needed. Our assay holds promising for more rapid pathogens related in clinical sepsis.